Development and Characterization of Press Coated Tablet of Flurbiprofen: A Chronotherapeutic Approach - Reddy, Matta Nalini Krishna (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The main objective of the present investigation was to formulate and characterize an oral pulsatile drug delivery system of flurbiprofen, for time dependent release, based on chronomodulated approach for the management of rheumatoid arthritis. Settings and Design: The drug delivery system was designed to deliver the drug with a lag time to release the drug when it could be most needful to patients of rheumatoid arthritis. Materials and Methods: Rapid release core tablets of flurbiprofen were prepared by wet granulation method with explotab as superdisintegrant. Then the press coated pulsatile tablets were formulated using different grades of hydroxypropyl methylcellulose (HPMC) E5, E15, and E50 in varying ratios. Pulsatile tablets were evaluated for pre- and post-compressional parameters. Then the tablets were optimized based on in vitro dissolution studies and lag time for drug release. Statistical Analysis used: One sample t-test was computed to compare the mean lag time obtained with different formulations with a standard of 6 h (360 min) as required time lag between administration of the dosage and drug release. Results: Core tablet formulated with explotab 4% showed 76.18 Â± 0.27% release in 10 min it was suitable for formulating into pulsatile release tablets. The formulation containing HPMC E50 at 1:2 ratio of core to coat has shown lag time of 6 h; thus, it was optimized and compiled with chronotherapeutic objective of rheumatoid arthritis. Conclusions: Pulsatile tablets of flurbiprofen were successfully formulated which provided a desirable lag time followed by desirable drug release.